Label-Free Proteomic Analysis of Smoke-Drying and Shade-Drying Processes of Postharvest Rhubarb: A Comparative Study - Liang, Wei; Chen, Yuan; Li, Xia; Guo, Fengxia; Sun, Jiachen; Zhang, Xuemin; Xu, Bo; Gao, Wenyuan (Frontiers in Plant Science, 2021)
Postharvest processing plays a very important role in improving the quality of traditional Chinese medicine. According to previous studies, smoke-drying could significantly promote the accumulation of the bioactive components and pharmacological activities of rhubarb, but so far, the molecular mechanism has not been studied yet. In this research, to study the molecular mechanisms of postharvest processing for rhubarb during shade-drying and smoke-drying, label-free proteomic analyses were conducted. In total, 1,927 differentially abundant proteins (DAPs) were identified from rhubarb samples treated by different drying methods. These DAPs were mainly involved in response and defense, signal transduction, starch, carbohydrate and energy metabolism, and anthraquinone and phenolic acid biosynthesis. Smoke-drying significantly enhanced the expression of proteins involved in these metabolic pathways. Accordingly, the molecular mechanism of the accumulation of effective ingredients of rhubarb was clarified, which provided a novel insight into the biosynthesis of active ingredients that occur during the rhubarb dry process.